AN EXAMINATION OF GST AND CENTRE-STATE FINANCIAL RELATIONS IN INDIA - Iti Dandona; Dr Praveen Tomar (IJRDO - Journal of Business Management, 2022)
Goods and Services Tax (GST) on 1 July 2017 is one of the big indirect tax reforms in the fiscal history of India. GST was conceived as a destination based consumption tax to subsume plethora of indirect taxes into a single seamless tax regime for enhanced tax efficiency, removal of cascading effect, convenience of doing business and development of a common national market. The reform has brought about a paradigm change in the Centre-State financial relations by providing concurrent taxing powers to the Centre and the States via a dual GST model comprising of CGST, SGST and IGST. It is a qualitative research which examines the changing character of fiscal federalism under GST system and changing dynamics of Centre-State financial interactions. The article discusses the constitutional and institutional reforms that have been introduced by the 101st Constitutional Amendment Act, 2016, especially the creation of the GST Council as a tool of cooperative federalism and intergovernmental fiscal coordination.